Synthesis and Stability Study of a New Bimetallic Complex (Ph3P)3CuMn(CO)5 - Ahmad, S.A.; Potratz, C.; Qadir, M.A. (Asian Journal of Chemistry, 2012)
The present work deals with the preparation and stability study of new bimetallic compound related to hetero bimetallic complex (Ph3P)3CuMn(CO)5. Mn2(CO)10 cleaved to KMn(CO)5 in the presence of Na/K alloy. CuCl and KMn(CO)5 reacted with triphenyl phosphine in the presence of THF at -78 ºC. It yielded a mixture of (Ph3P)3CuCl and KMn(CO)5. At 0 ºC, this mixture reacted and produced (Ph3P)3CuMn(CO)5 and Ph3P. New product (Ph3P)3CuMn(CO)5 was found very sensitive to oxidation. It decomposed into (Ph3P), Cu and Mn2(CO)10 under vacuum, at room temperature.